CO2 capture and water use efficiency in Opuntia stricta (Haw.) at different seasons and evaluation times - Souza, José Thyago Aires; Araújo, Jucilene Silva; Félix, Evaldo dos Santos; Alves, Rita de Cássia; Oliveira Filho, Tarcísio José de; Lira, Elder Cunha de (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The forage cactus Mexican Elephant Ear is widely incorporated into the animal productive chain of the northeast region of Brazil. However, there is a lack of studies on the physiological dynamics of this cactus. Therefore, this study was conducted at the Estação Experimental Prof. Ignácio Salcedo of the Instituto Nacional do Semiárido (INSA), in Campina Grande, State of Paraíba, Brazil. The aim of this study was to evaluate CO2 uptake and water-use efficiency levels in Opuntia stricta (Haw.) during different seasons and evaluation times. The treatments were distributed using a 24×2 factorial arrangement, which corresponded to the evaluation of gas exchange processes for 24 hours in the rainy (June) and dry (December) seasons. The evaluated parameters were stomatal conductance, transpiration and CO2 uptake rate, internal CO2 concentration, instantaneous water-use efficiency and intrinsic water-use efficiency. The results revealed that gas exchange in the forage cactus was more intense during the rainy season, with good stability, than the low exchange levels during the dry season. Regardless of the season, the CO2 uptake peaked between 24:00 and 02:00. In addition, this range of time is the most suitable to conduct analyses under field conditions.